BEING IN HARMONY : Biblical Vision of Interconnected Existence - Kanayankal, Saji Mathew (Journal of Dharma, 2011)
The current "environmental crisis" is not simply a calamity or disaster or a crisis of certain particular phenomenon in the world. It is, rather, a fundamental deterioration of the integrity and comprehensiveness of the total rhythmic, interdependence and coherent flow of the entire ecosystem. The root of this crisis remains on the inability of the human being to place hirn/her self within a broadly conceived ecological context. Therefore, in search for a plausible response to environmental crisis, we have to retrieve or reconsider different premises on human superiority and various hypotheses - philosophical, theological, and religious - on his/her existence and role in the universe. In this pursuit, the religious symbols, traditions and practises of Christianity have also been challenged.